2007
DOI: 10.1007/s10140-006-0566-9
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis secondary to diverticulitis

Abstract: Necrotizing fasciitis is a rare, rapidly progressive infectious process primarily involving the fascia and the subcutaneous tissue, with thrombosis of the cutaneous microcirculation. We present a case of necrotizing fasciitis secondary to diverticulitis in an immunosuppressed patient with rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition to malignancy, enterocolitis has also been identified as a risk factor for the development of gas gangrene [11] , [12] , [13] . It has been demonstrated that gastrointestinal inflammation causes hypoxia [14] , and it may be the hypoxic environment that helps propagates spore formation and the spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to malignancy, enterocolitis has also been identified as a risk factor for the development of gas gangrene [11] , [12] , [13] . It has been demonstrated that gastrointestinal inflammation causes hypoxia [14] , and it may be the hypoxic environment that helps propagates spore formation and the spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus and peripheral vascular disease are common predisposing factors in poly-microbial NSTI [32]. Other predisposing factors include obesity, chronic renal failure, human immunodeficiency virus (HIV) infection, alcohol abuse, abscess, intravenous (IV) drug use, insect bites, recent surgical incisions, and perforation of the gastrointestinal tract [29,33,34]. Interestingly, an inciting event is never identified in 20%-50% of the patients [14,15,35].…”
Section: Microbiologymentioning
confidence: 99%
“…Nonetheless, the epidemiology of type I NSTIs seems to indicate that the major pathophysiologic factor in development of such an infection is on overall state of poor health or immunocompromise. Thus, these polymicrobial NSTIs of the trunk, perineum, or neck are associated with diabetes and peripheral vascular disease, 10 obesity, chronic renal insufficiency, alcohol abuse, existing abscesses, [21][22][23][24] blunt trauma, chicken pox, HIV or AIDS, and, as mentioned above, IV drug abuse. 2…”
Section: Pathophysiologymentioning
confidence: 99%